DIFFERENTIAL DIAGNOSTICS OF BACTERIAL AND VIRAL LYMPHADENITIS IN CHILDREN - S.S. Antonova; V.V. Botvin'eva; I.G. Sitnikov ("Paediatrician" Publishers LLC, 2008)
The article focuses on the analysis of experience of differential diagnosis of bacterial and viral lymphadenitis in children. Diagnostics of different types of lymphadenitis in 70 pediatric patients was carried out with procalcitonin detection in blood plasma, held by immunochromatographic expressbtesting (brahms PCT Q). Key words: procalcitonin, viral lymphadenitis, bacterial lymphadenitis.